Kesulitan Membaca Permulaan Siswa Kelas I SDN 105 Pekanbaru - Hana Fitria; Febrina Dafit (Civiliza Publishing, 2022)
This study aims to determine the difficulty of reading the beginning of grade I students, the factors that influence the difficulty of reading the beginning of the students of class I, and how to overcome the difficulty of reading the beginning of the students of class I SDN 105 Pekanbaru. The type of research used is a case study with a qualitative approach. The subjects in this study were class ID students and class ID teachers at SDN 105 Pekanbaru. Data collection techniques were carried out by tests, observations, interviews, and documentation. The data collection instruments in this study were test sheets, observation sheets, interview guidelines, and document review. The results showed that 3 students had difficulty reading the beginning. The types of difficulties experienced by students are difficulties in recognizing and distinguishing letters, difficulties in spelling words that contain diphthongs, consonants, and affixes, reading haltingly, and pronouncing wrong words. Factors that influence students' initial reading difficulties are psychological factors and environmental factors. Psychological factors occur due to lack of motivation, namely students lack of motivation and parental attention and environmental factors occur because of the background of students at home, namely students do not take Kindergarten (TK) education and students do not repeat learning at home. The way or solution in overcoming students' initial reading difficulties is by using learning media, giving rewards (gifts), providing support and motivation, and including reading lessons.